1994
DOI: 10.2118/17328-pa
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium Swelling and Syneresis Properties of Xanthan Gum/Cr(III) Gels

Abstract: Syneresis and swelling of xanthan gum-Cr(Il!) gels in contact with reservoir brine correlate withcomposition of the gel, temperature and pH.ABSTRACT Swelling and syneresis behavior was measured by equilibrium swelling of xanthan gum-Cr(lII) gels that had been aged for over 100 days. The dependence of swelling on pH, temperature and presence of calcium ion was determined. Degree of swelling varied from +66% to -71 % over the range of parameters investigated. Theoretical considerations are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…This indicates that the effect of the inorganic cations on the carboxyl group is no longer the determining factor for the volume changes of the gel. According to polymer network theories [16], the swelling or the syneresis of a polymer network is governed by the mixing potential and the elastic potential. The mixing potential favors the dispersion of network chains into the solvent and hence swelling, and the elastic potential represents the elastic force imposed by the crosslinks which resists the change of the network chains from their unstrained state.…”
Section: Effect Of Inorganic Salts On the Syneresismentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the effect of the inorganic cations on the carboxyl group is no longer the determining factor for the volume changes of the gel. According to polymer network theories [16], the swelling or the syneresis of a polymer network is governed by the mixing potential and the elastic potential. The mixing potential favors the dispersion of network chains into the solvent and hence swelling, and the elastic potential represents the elastic force imposed by the crosslinks which resists the change of the network chains from their unstrained state.…”
Section: Effect Of Inorganic Salts On the Syneresismentioning
confidence: 99%
“…Gales et al [16] investigated the stability of xanthan gum/Cr 3+ gel, and they showed that the increase of Cr 3+ used in the gel led to the high degree of syneresis. They therefore concluded that reducing the crosslinking density is facilitated to decrease the syneresis, and pointed out the appropriate amount of crosslinking agent was the precondition to ensure the gel possessing the excellent stability.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the composition, a syneresed gel may occupy as little as 5% of the initial solution volume 6 . As Gales 33 explains, syneresis usually occurs in a gel prepared from a relatively dilute polymer solution, which has a relatively low mixing potential compared to a gel with higher polymer concentration. When the gel is first formed (at the gel point) the crosslinking density is usually low so that the elastic potential is still smaller than the mixing potential.…”
Section: Spe 86548mentioning
confidence: 99%
“…Among biopolymers, xanthan gum (XG) is by far the most studied 4–18 due to its physical and chemical properties: the ability to increase the viscosity, stability in extremely saline environment and high temperatures and mechanical shear conditions. These properties make this biopolymer interesting for application in conformance control treatment 12 …”
Section: Introductionmentioning
confidence: 99%